Government of Meghalaya Ninth Five Year Plan 1997-2002 and Annual Plan—1997-98 Draft Proposals Volume II Part - V Energy - Planning Commission (Planning Commission, 1997)
Aiming at maximising benefits from the existing installed capacity in the state, Me.S.E.B. formulated two schemes for Renovation & Modernisation of Umiam State-I & State-II Power Station by engaging M/S Japan Consulting Institute as Consultants. Both the schemes were submitted to OECF for funding during 8th plan period. OECF agreed to fund R & M scheme for Umiam State-I power station with effect from 1997-98. the estimated cost of the scheme is Rs.63 crores. Persuasion for providing fund by OECF for the R & M scheme of Umiam State-II Power station during 9th is continuing. It is anticipated that OECF would agree to fund the scheme during 1999-2000. The estimated cost of the scheme is Rs.31 .40 crores. Renovation works of Umiam State-Ill Power House at an estimated cost of Rs.740 Lakhs has also been considered during 9th Plan. A token provision of Rs.50 Lakhs for renovation and improvement of station auxiliary supply system for Urniam-Umtru State-IV power station has also been kept during 9th plan period.
Power Non-Conventional Sources of Energy Integrated Rural Energy Programme (IREP)